Entrelazamiento y transiciones de fase en un BEC de polaritones excitónicos confinados en una nanocavidad de cristal fotónico (2013)
ABSTRACT: In this work we study a polariton{exciton system confined in photonic crystal nanocavity with embedded quantum dot. Using a separable state of the type BCS, for the matter subsystem, product by a coherent state, for the photonic mode, we compute the ground state energy of N polaritons. Also, we characterize the quantum coherence in the system using entanglement and discord, calculated both from the pair density matrix. Finally, we introduce temperature and magnetic field to our model and we obtain signatures of phase transitions in the quantum correlations of the system.